Regression Analysis of Coherence between Concurrent EEG-EEG and EEG - CPPG Signals from Prefrontal Cortex During Music Evoked Emotions - Shriram, Revati; Baskar, V Vijaya; Martin, Betty; Sundhararajan, M; Daimiwal, Nivedita (Journal of Information Science and Engineering, 2019)
This paper summarizes the results of experiment that focus on effect of music evoked emotions on mean squared coherence and phase coherence between two signals with same nature (electrical brain signal - EEG) and the two signals with different nature (EEG and hemodynamic brain signal CPPG). Regression analysis was carried out to find out the mathematical relation between mean squared coherence and phase coherence estimated between the two signals captured from prefrontal cortex and the physiological parameters. Number of synaptic connections between the two measurement sites/ signals and its strength is reflected in the coherence. It is a quantitative measure of association between the two simultaneously acquired signals as a function of frequency. Physiological parameters studied by the authors are SBP, DBP, HR, Blood Glucose and BMI. These are some of the potential biological markers closely related to emotional response. Data was collected from twenty multi-lingual subjects of both the genders with Mean_(age) = 39.25 years and SD_(age) = 11.625 years. No strong correlation was found between the coherence (calculated between EEG-EEG and EEG-CPPG) and the physiological parameters studied during the various emotional states. It was observed that MS Coherence between the signals with similar nature is higher than it in between the signals with dissimilar nature. T-paired test was carried out to show that the means of these two coherences is different. Coherence between EEG-EEG was compared with coherence between EEG-CPPG and it was observed that they are very different (p ＜ 0.001), were as when coherence between EEG-EEG (or EEG-CPPG) is compared with coherence between EEG-EEG (or EEG-CPPG) p-value was ＞ 0.05. This technique can be applied to wider population in the field of clinical neuroscience with or without any known neurological disorder. More connectivity measures can also be included to study music evoked emotions or stroop task.